2020
DOI: 10.2106/jbjs.20.00246
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation and Disparities in Total Joint Replacement Use for Medicare Beneficiaries: 2009 to 2017

Abstract: Background: Little is known about how the geographic variation and disparities in use of elective primary total hip and knee replacements for Medicare beneficiaries have evolved in recent years. The study objectives are to determine these variations and disparities, whether Black Medicare beneficiaries have continued to undergo fewer total hip replacements and total knee replacements across regions, and whether disparities affected all Black beneficiaries or mainly affected socioeconomically disadv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…We chose dual eligibility as a proxy for socioeconomic status because of its strong dependence on having low income. 7 , 30 , 31 We controlled for the calendar year and patient-level risk factors, such as age, sex, and binary indicators for 24 chronic conditions (eTable 1 in the Supplement ), in a multivariable analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose dual eligibility as a proxy for socioeconomic status because of its strong dependence on having low income. 7 , 30 , 31 We controlled for the calendar year and patient-level risk factors, such as age, sex, and binary indicators for 24 chronic conditions (eTable 1 in the Supplement ), in a multivariable analysis.…”
Section: Methodsmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 This avoidance may reduce the opportunity for beneficiaries from racial/ethnic minority groups, especially those from lower socioeconomic strata (collectively known as socially disadvantaged beneficiaries), to undergo joint replacement, thereby exacerbating the persistent disparities. 7 These concerns are supported by several factors, including complex health needs, 8 the likelihood of postoperative complications and readmissions, 9 , 10 and increased costs among socially disadvantaged patients; all of these factors are associated with higher spending and lower quality scores for hospitals. This CJR model–associated mechanism for worsening of use disparities adds to other mechanisms, such as patient preferences guided by inadequate information, 11 , 12 uncertain expectations, 13 and worse outcomes among family and friends, 14 as well as clinician biases while recommending surgical procedures, 15 , 16 and geographic factors associated with surgical access.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, among CJR hospitals, although we found evidence of patient selection in elective admissions, it is not clear why providers choose fewer Black patients. Health disparities and social determinants of health across racial groups in the CJR model have been well documented, 27,28 and are a persistent systematic issue in health care 29,30 . However, it is unknown whether providers' decisions to admit patients are due to racial disparities in health and access or partially based on racial discrimination and/or implicit bias.…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities in the use of TJA are well known. A study by Thirukumaran et al ( 9 ) used Medicare claims data from 2009 to 2017 to compare elective TJA rates among Black and White beneficiaries. The authors found that Black beneficiaries were significantly less likely to undergo TJA than White beneficiaries ( 9 ).…”
Section: Racial Disparities In Tja Usementioning
confidence: 99%